Bringing Genius Hour to your library implementing a schoolwide passion project program - Rush, Elizabeth Barrera (Libraries Unlimited, an imprint of ABC-CLIO, LLC, 2018)
"'Genius Hour' is a name for a movement in education where students are allowed to regularly use a portion of class time to learn about whatever they want in school. Bringing "Genius Hour" to Your School Library is meant to provide information pertaining to elementary and secondary school librarians, guidance on how to initiate and manage a school-wide Passion Project program in the library, and develop the solidly coherent, meaningful library program."--Provided by publisher.